1994
DOI: 10.1016/s0007-8506(07)62160-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Surface Generation in Orthogonal Ultraprecision Machining

Abstract: Los Alamos National Laboratory, an affirmative actiordequal opportunity empldyer, is operated by the University of California for the U.S. Department of Energy under contract W-7405-ENG-36. By acceptance of this article, the publisher recognizes that the U.S. Government retains a nonexclusive, royalty-free license to publish or reproduce the published form of this contribution, or to allow others to do so, for U.S. Government purposes. The Los Alamos National Laboratory requests that the publisher identify thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…As f 2 /r n is the uncut chip thickness at the part of the cutting edge where the feed mark peaks are created [4], the inequality suggests a critical uncut chip thickness to cutting edge radius ratio at the finished surface, %0.15, below which edge sharpness determines finish. 0.15 is within the range of critical uncut chip thickness to cutting edge radius ratio for transitions from cutting to ploughing in precision orthogonal cutting studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 71%
“…As f 2 /r n is the uncut chip thickness at the part of the cutting edge where the feed mark peaks are created [4], the inequality suggests a critical uncut chip thickness to cutting edge radius ratio at the finished surface, %0.15, below which edge sharpness determines finish. 0.15 is within the range of critical uncut chip thickness to cutting edge radius ratio for transitions from cutting to ploughing in precision orthogonal cutting studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 71%
“…The force in case E8 is typically double that of E1. This follows logically, but when the material removed gets extremely small, such as single atoms, some have predicted that this trend of decreased force with decreased material will not necessarily hold due to the atomic interactions not seen in large-scale milling [15][16][17].…”
Section: Cutting Force Measurementsmentioning
confidence: 99%
“…Below the critical value, large increases in specific forces have been measured [2,3]. Changed surface appearances from clean cut to burnished have been reported [4,5]. Experimental and theoretical studies have indicated the critical value of a c /r e to be between 0.1 and 0.5, depending on material machined and cutting conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%